استخدام برنامج سويش ماكس الحاسوبي لتعليم مهارة الكلام - Supri Yanto (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2017)
This researche discuss about Arabic teaching using SWISHmax Computer Program specifically on speaking skill. Because conversational skill is one of the most important language skills in mastering a language. In addition, teaching this above mentioned skill also means teaching how to communicate the underlying activities and convey messages to others. Furthermore, this condition led to the emphasis of teaching speaking during the second world war since soldiers needed to get accurate information for control of the battlefield in an occupied site. As a result, they tried to invent a method of teaching second language with a variety of interesting teaching media to master the language quickly. Based on the experience of second-language instruction, then the media have made the second-language teaching in various countries around the world, including the Arabic language become the official language of religion and the internationally used language at the United Nations. Nonetheless, in Arabic teaching there are still many students can’t master it well, specifically on mastering speaking skill at the elementary level. This lack speaking skill is caused by the medium teaching used by the teacher is not effective. Therefore, the researcher tries to solve that problem by making the media which is more interesting and fun, that is SWISHmax Computer Program. Keywords: SWISHmax Computer Program, teaching, speaking skill.